Kemampuan Pemecahan Masalah Matematika Siswa SMP dalam Menyelesaikan Soal Sistem Persamaan Dua Variabel (SPLDV) - Sumarni, Ai; Nurcahyono, Novi Andri; Setiani, Ana (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
Mathematical problem-solving abilities are important to support the development of 4C skills (Communication, Collaboration, Critical Thinking, Problem-Solving, Creativity, and Innovation) in the 21st century. However, in reality, students' ability to solve problems is still relatively low and does not meet expectations. This research aims to identify students' mathematical problem-solving abilities in solving System of Equations in Two Variables (SPLDV) problems. The research method used is descriptive quantitative, with data collection through tests in the form of descriptions. The population of this study was all students in class VIII in one of the junior high schools in Sukabumi Regency, with a sample taken of 24 students from class VIII. The research results showed that the average student score was 34.5, with the majority of students being in the low category at 87.5%, and only a few students were able to reach the medium category with a percentage of 4.17% and high with a percentage of 8.33%. Analysis of the problem-solving stages shows that although 70.83% of students were able to understand the problem, 41.67% could plan the problem, only 12.5% succeeded in solving the problem, and 8.34% could check the solution. These results also show that the students' mathematical problem-solving abilities in solving System of Equations in Two Variables (SPLDV) problems at this school are mostly in the low category and still need a lot of improvement.